Pengaruh Penerapan Corporate Governance Terhadap Kondisi Kesulitan Keuangan - Stephanus Andi Adityaputra (Ultima Accounting : Jurnal Ilmu Akuntansi, 2017)
This study examined the effect ofthe implementation of corporate governance on the condition of the financial distress of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The implementation of corporate governance proxied with the proportion of managerial ownership, proportion of institutional ownership, number of the boards of directors, proportion of independent commissioners, and existence of the audit committee. Samples used in this study was manufacturing companies listed on the Indonesia Stock Exchange (IDX) with 2012 up to 2016 as an observation period. The total study samples was 48 firms with 96 firm year are determined by the method of purposive sampling. This study used Logistic Regression to examine the effect of the implementation of corporate governance of the condition of the company's financial distress. The results of this study indicated that The number of the boards of directors and the proportion of independent commissioners variables were not proven to have significant influence on the condition of the company's financial distress. The proportion of managerial ownership, the proportion of institutional ownership, and the existence of the audit committee variables proved to have a significant influence on the condition of the company's financial distress with a positive influence. Keywords: board of directors, independent commissioners, managerial ownership, institutional ownership, audit committee, financial distress, logistic regression